Béla Tarr, the time after - Rancière, Jacques (Univocal., 2013)
From Almanac of Fall (1984) to The Turin Horse (2011), renowned Hungarian filmmaker Bela Tarr has followed the collapse of the communist promise. The "time after" is not the uniform and morose time of those who no longer believe in anything. It is the time when we are less interested in histories and their successes or failures than we are in the delicate fabric of time from which they are carved. It is the time of pure material events against which belief will be measured for as long as life will sustain it. -- Provided by publisher